Pengaruh Likuiditas, Leverage, dan Profitabilitas terhadap Kebijakan Dividen pada Sektor Consumer Non Cyclical yang Terdaftar di Bursa Efek Indonesia - Jesika Resky Permana Andastuti; Mentiana Sibarani (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
The capital market is one of the places where companies obtain funds to support their operations and ensure their survival in an increasingly competitive business environment. Furthermore, the capital market also provides a platform for investors to channel their funds into financial instruments in the hope of achieving returns or profits in the form of dividends and capital gains. This study aims to analyze and examine the influence of liquidity, leverage, and profitability on dividend policy in companies within the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. This research employs a quantitative approach with a causal-comparative method, grounded in the philosophy of positivism. The population consists of all companies in the consumer non-cyclical sector listed on the IDX main board. The sampling method used is purposive sampling, based on specific criteria, resulting in a sample of 30 companies. The data used in this study are secondary data, obtained indirectly through sources such as data published by the Indonesia Stock Exchange. The statistical method applied is multiple linear regression, analyzed using SPSS version 26.0. The results of the study indicate that liquidity, leverage, and profitability simultaneously have a positive and significant influence on dividend policy. Partially, each of these variables liquidity, leverage, and profitability also has a positive and significant effect on dividend policy in the consumer non-cyclical sector during the 2022–2024 period.